1976
DOI: 10.1080/00218467608075086
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Viscoelastic Behavior of Styrene-Diene Block Copolymers in Pressure Sensitive Adhesives

Abstract: Linear (SDS) and radial (SD), block copolymers of styrene (S) and dienes (D = butadiene or isoprene), varying in composition and molecular weight, were formulated as pressure sensitive adhesives. The morphology of these compositions was determined by electron microscopy of ultra-thin scctions and dynamic viscoelastic measurements were made at 35 Hz between -90" and +14O"C or higher. Pressure sensitive tack and holding power were determined and interpreted in terms of morphological and rheological properties.A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…( 4 ) . G,9, = V;(p/M,)RT(l + 2.5C + 14.1Cz) ( 5 ) In eq. (5), C is the volume fraction of polystyrene domain in the entire composition and V2 is the volume fraction of polymer in the tackified polyisoprene phase.…”
Section: Rubbery Plateaumentioning
confidence: 97%
“…( 4 ) . G,9, = V;(p/M,)RT(l + 2.5C + 14.1Cz) ( 5 ) In eq. (5), C is the volume fraction of polystyrene domain in the entire composition and V2 is the volume fraction of polymer in the tackified polyisoprene phase.…”
Section: Rubbery Plateaumentioning
confidence: 97%
“…This was explained as the highest modulus that still allowed the adhesive to be sufficiently compliant to come into molecular contact with a substrate and form dispersive interfacial bonds. Investigators who followed Dahlquist have accepted this requirement [12][13][14][15][16], termed the "Dahlquist Criterion of Tack", even though the true criterion is defined as a dimensionless quantity.…”
Section: List Of Abbreviationsmentioning
confidence: 99%
“…Various authors [18][19][20][21] have found that one effect of a tackifier in pressure-sensitive adhesives of natural rubber, polyacrylates and styrene-diene blockcopolymers is the reduction of the modulus in the plateau zone. This is achieved by an increase in the entanglement spacing in full agreement with the results presented here.…”
Section: Maximum Adhesive Strength and Tackmentioning
confidence: 99%